Can signal delay and advertising lead to profit? A study on sporting - Wu, Yannian; Yim, Brian H.; Lu, Chaoyun; Mao, Luke; Zhang, James J. (Frontiers in Psychology, 2023)
Introduction Live sporting event streaming (LSES) is becoming popular not only among consumers but also among sponsors. At the same time, influenced by China’s convenient mobile terminals, the paid membership system for live broadcasting has also attracted the attention of marketers and scholars. To promote financial sustainability, we analyzed the internal mechanism of profitability in LSES based on stimulus-organism-response (SOR) theory and two-sided market characteristics. Specifically, we considered advertisement and delay the stimuli (S), arousal and attention as the organism variables (O), and intention to become a paying member as the response (R). Methods We used an online survey questionnaire to collect data from 430 Chinese LSES viewers during the 2021 European Cup. We used SPSS Amos v. 26 to conduct structural equation modeling (SEM) and bootstrapping to test the model. Results The results show that the direct paths from advertisement and delay to behavioral intention were not significant and that these relationships only became significant via the mediating variables of arousal and attention. Compared to advertising, delay had a stronger indirect effect on behavior. Arousal and attention generated a chain intermediary mechanism in which the presence of attention was necessary. Discussion First, LSES platforms should follow Internet development trends and create higher economic value by using precise advertising strategies. Second, LSES platforms should make full use of 5G mobile communication technology to maximize profit. Third, LSES platforms must pay attention to the intermediary mechanism of arousal and attention. Streaming media must provide high-quality events in order to keep target audiences excited.